‘Counselling is the only thing to do’: healthcare providers’ experience of Kangaroo Mother Care in Bangladesh – a qualitative study - Ylva Thernström Blomqvist; Syed Moshfiqur Rahman; Mats Målqvist; Johanna Sjömar; Taqbir Us Samad Talha (BMJ Public Health)
Aim To explore healthcare providers’ (HCPs) experiences of facility-initiated kangaroo mother care (KMC) in Bangladesh.Methods An explorative qualitative study based on 11 semistructured interviews with HCPs from 2 hospitals in Dhaka was conducted. Nurses, medical officers and paediatric consultants were representing the HCPs. Inductive, qualitative content analysis was used.Results Supporting KMC needs to be a continuous process that requires a high level of commitment from healthcare staff. Optimal implementation is, however, challenged by structural conditions such as shortage of staff, separation of mother and child, and incomplete follow-up, which need to be addressed to support KMC.Conclusion Findings from this formative research can help in designing interventions for scaling up KMC in Bangladesh by paying attention to the crucial role of HCPs and giving them training on the importance of continuous and repeated counselling to both mother and family. To enhance motivation, involving nurses in follow-up care is essential, alongside strengthening the health system for families living far away and tracking those not attending follow-up. Furthermore, after this study was conducted, the WHO updated its recommendations regarding KMC. This means that the current study, in combination with the WHO’s new recommendations, can be used for the development of new guidelines for KMC in clinical practice in Bangladesh.